Análise do impacto logístico no setor de transporte de cargas: estudo de caso com a introdução de caminhões elétricos - Dallepiane, Patrícia Gomes (2021)
Efficient and economical cargo transportation is an important factor to contribute to the development of the economy, competitiveness in the market and the reduction of expenses in the logistics of companies. Electric trucks provide a new mobility alternative, due to the advantages related to the vehicle's energy efficiency, noise reduction in traffic, reduction of pollutant emissions and for registering lower supply and maintenance costs compared to traditional trucks. In addition to seeking to build a sustainable economy through recharges by renewable energy sources. Thus, the objective of this dissertation is to carry out an analysis of the logistical impact with the insertion of electric trucks for the transportation of loads of drinks. This study tends to develop analysis of possibilities to contribute to decision making in companies, with regard to the replacement of diesel trucks by electric ones, through the analysis of planned route profiles for trucks to operate during the working day, economic evaluation with supply and fleet maintenance, application of the cost of mitigating carbon emissions when replacing diesel oil with electricity, analysis of expenses for recharging trucks in different tariff modalities and ending with the application of the AHP method to check the degree of importance of trucks diesel and electric. The study is based on information collected at the company FRUKI in Lajeado and at distribution centers located in Rio Grande do Sul. The analysis of each criterion aims to demonstrate that the fleet replacement process can be a viable alternative for companies, due to the economy generated during its operation and reduction in the emission of pollutants.